Pemahaman Siswa Mengenai Penggunaan Media Gambar dalam Pembelajaran IPA tentang Sistem Pernapasan Manusia di Kelas V MI Al-Hidayah Jember - Adilah Kaharani Putri; Muhammad Suwignyo Prayogo; Intan Azzahro; Siti Royhana (Universitas Palangka Raya, 2025)
The goal of this research was to evaluate the effectiveness of the use of visual media in the form of images in supporting science learning, especially on material about the human respiratory system, in class V MI Al Hidayah Jember. The approach used a qualitative descriptive approach with direct observation techniques at the research site. The reason for utilizing image media is to introduce more interesting learning methods and help students understand the material more easily. This research focused on examining the extent to which picture media was able to increase students' enthusiasm and interest in learning. Data were acquired through a series of observations, conversations with teacher and documentation of student learning outcomes. A total of 25 students from class V were used as participants in this activity. The results showed that picture media was able to clarify the concept of respiratory organs, make it simper for pupils to recallr the contents of the lesson, and increase their activeness in the process of learning, Before using visual media, only 40% of students reached the KKM, but after its application, the figure increased to 84%. This finding shows that picture media is a very effective tool in helping students understand abstract science material.